FRAMEWORK OF PROJECT QUALITY MANAGEMENT - Rahmana, Arief (CENTRAL ASIA AND THE CAUCASUS, 2022)
This paper proposed the framework of project quality management based on A Guide to the Project Management Body of Knowledge (PMBOK® Guide) as a comprehensive strategy to ensure our projects meet specifications. roject quality management is essential aspect for measuring quality of all project activities and taking corrective action to gain desired quality. As we know that quality management also help us to control project cost, develop standards, and determine ways to achieve and confirm those standards. Implementation of project quality management has several benefits i.e. quality product, customer satisfaction, increased productivity, financial gains, remove silos, and better teamwork. Beside that effective project quality management provide framework for our team consistently delivers quality of product and services. Furthermore it also lowers the risk of rejected product, unsatisfied stakeholders, and unhappy clients.